Associations between several sites of cancer and twelve petroleum-derived liquids. Results from a case-referent study in Montreal. - Siemiatycki, Jack; Dewar, R; Nadon, Louise; Gerin, M; Richardson, Lindsey; Wacholder, S (Scandinavian Journal of Work, Environment & Health, 1987)
A population-based case-referent study provided information on the associations between several types of cancer and 12 petroleum-derived liquids. All site-exposure combinations were investigated. The most interesting results concerned the following combinations: leaded gasoline-stomach cancer, aviation gasoline-kidney cancer (and the possible implications of this association for a similar effect of unleaded automotive gasoline), mineral spirits-squamous-cell cancer of the lung, diesel fuel-nonadenocarcinoma lung cancer, lubricating oils-squamous-cell lung cancer, cutting fluids-bladder cancer, other mineral oils-bladder cancer, mineral spirits-prostate cancer, diesel fuel-prostate cancer, and lubricating oils-prostate cancer.